Aquatic Plant Genomics: Advances, Applications, and Prospects - Shiqi Hu; Gaojie Li; Jingjing Yang; Hongwei Hou (International Journal of Genomics)
Genomics is a discipline in genetics that studies the genome composition of organisms and the precise structure of genes and their expression and regulation. Genomics research has resolved many problems where other biological methods have failed. Here, we summarize advances in aquatic plant genomics with a focus on molecular markers, the genes related to photosynthesis and stress tolerance, comparative study of genomes and genome/transcriptome sequencing technology.